(untitled) (Cadernos de Sociomuseologia, 2022)
In this edition of Cadernos de Sociomuseologia, the central theme is the relationship between museology and Cultural diversity. Analyzing from the changes that the field of museology is undergoing to the discussion of concrete cases of changes in the focus of institutions, going through historical examples of action in this sense, the articles that make up this edition bring to the debate different facets of diversity. This multiplicity points out how these changes in the way museums and museologists work can represent the emergence of new themes, new ways of knowing and new protagonisms, which bring with them many possibilities and opportunities, as well as an equal number of challenges. The recognition and appreciation of the cultural diversity present in the various spaces has been, in recent times, one of the main points of interest in Museology. Although museums have, throughout their trajectory, often acted as one of the most privileged tools in the construction of national identities that exclude portions of the population considered undesirable from their scope, in more recent times, in many institutions, the same spaces have been opened to broader conceptions of belonging, which recognize diversity as the basis of any society. This change of orientation that seeks a conscious and critical action towards the recognition and respect for diversity(s) is one of the bases that has sustained Sociomuseology.